A 98 years old super elderly coronary heart disease patient treated with enhanced external counterpulsation: a case report - Lin, Cailong; Lai, Yingying; Xu, Jiajia; Li, Min; Guo, Yan; Huang, Jianyu; Xu, Lin (Frontiers in Cardiovascular Medicine, 2025)
Enhanced external counterpulsation (EECP) is a safe, non-invasive, economic and effective assisted circulation technique. It not only can improves multisystem disorders, but also reduces adverse event rates. EECP utilizes electrocardiogram-gated sequential inflation of cuffs wrapped around patient's lower extremities to increase blood flow perfusion of heart, which can improve myocardial ischemia of patients with coronary heart disease (CHD). Patients with CHD or heart failure or sleep disorder are suitable to receive EECP. But there are few reports on super elderly people. This is the first reported case of a 98-year-old patient with CHD, who accepted EECP. Patient was presented to hospital with complaints of “intermittent chest tightness for 12 years, worsening for 20 days.” His medical history included lacunar infarction, as well as type 2 diabetes mellitus and hypertension. For the elderly patients reported in this case, the efficacy of medicine was limited and the surgical risk was high. After performing a course of EECP, The patient's symptoms of CHD adverse psychological conditions and sleep quality were improved. This report proved the effectiveness and safety of EECP to treat such super elderly patients with CHD, which provided evidence for the clinical application of EECP in such patients.